Factors influencing agent's repurchase and revisit intention to Proboscis Lodge Bukit Melapi (PLBM) / Stefanie Herman Juadi - Herman Juadi, Stefanie (2011)
The purpose of this study is to investigate the factor influencing agents repurchase and revisit intention to Proboscis Lodge Bukit Melapi. Four perceived factors (Perceived Quality, Perceived Risk, Perceived value and Perceived Attractiveness) with satisfaction and revisit intention were generated. The model was developed on the basis of existing theoretical model which focus on marketing and tourism. Based on the regression analysis it shows that, perceived risk, perceived value and perceived attractiveness gave positive mediating effect with satisfaction however perceived quality gave negative mediating effect with satisfaction. Satisfaction on the other hand also gave positive mediating effect with agents revisit and repurchase intention. The overall result, factors influencing satisfaction and revisit intentions will act as an input to improve PLBM performance.